SAT0473 Clinical and echocardiographic associates of all-cause mortality and cardiovascular outcomes in patients with systemic sclerosis. (12th June 2018) - van Wijngaarden, S.E.; Boonstra, M.; Bloem, B.; Cassani, D.; Tanner, F.C.; Jordan, S.; Distler, O.; Delgado, V.; Bax, J.J.; de Vries-Bouwstra, J.K.; Ajmone Marsan, N.
Abstract : Background: Cardiac events are an important cause of mortality in Systemic Sclerosis (SSc), but its diagnosis remains challenging. Left ventricular global longitudinal strain is a novel parameter derived from speckle tracking echocardiographic analysis which has been proposed to identify patient at higher risk of cardiac events. Objectives: We aimed to identify clinical and echocardiographic (including GLS) parameters associated with all-cause mortality and cardiovascular events in SSc patients. Methods: 408 SSc patients (344 females, age 54±14 years.) were prospectively evaluated at baseline and follow-up (FU time 3.3 years. [IQR 1.8 to 5.5]). Cardiovascular events included: heart failure, cardiac infarction, coronary interventions, device implantation, arrhythmias, cerebral infarction, peripheral ischaemic vascular disease. Results: All-cause mortality (n=37) or cardiovascular events (n=57) occurred in 84 patients. At baseline, these patients were older (59±14 vs. 53±14 years., p<0.001), more often male (24 vs. 13%, p=0.018), more often had skin pigment changes (21 vs. 5%, p=0.011), coronary artery disease (11 vs. 3%, p=0.001), holter abnormalities (45 vs. 24%, p≤0.001), increased ESR (24 [IQR 14 to 46] vs. 11 [IQR 6 to 25], p<0.001), worse NT-proBNP (151 [IQR 60 to 644] vs. 82 [IQR 51 to 145] ng/L, p<0.001), worse lung function test results (FVC 92±19 vs. 104%±21%, p<0.001; DLCO 55±17 vs. 70%±19%, p<0.001), worse left ventricular diastolic function (E/E-prime ratio 9.9 [IQR 6.7 to 10.2] vs. 7.8 [IQR 6.4 to 9.7], p<0.001), higher systolic pulmonary artery pressure (31±12 vs. 25±7 mmHg, p<0.001) and lower GLS (−18.8 [IQR −20.3 to −19.5] vs. −21.1 [IQR −22.1 to −20.0]%, p<0.001). In a multivariate cox-regression analyses, age (HR 1.029, 95% CI 1.006 to 1.052), female sex (HR 0.527, 95% CI 0.302 to 0.922), NT-proBNP (HR 1.000, 95% CI 1.000–1.001), DLCO (HR 0.973, 95% CI 0.961–0.986) and GLS (HR 1.281, 95% CI 1.172–1.399) were independently associated with outcome. After dividing patients into groups according to median GLS (−20.9%) and elevated NT-proBNP (>200 ng/L), survival rates were lower and cardiovascular events increased when GLS was impaired and worsened when NT-proBNP was elevated (Log-rank p<0.001). Conclusions: In SSc patients, next to age, DLCO and NT-proBNP, GLS strongly associates with all-cause mortality and cardiovascular events, indicating that these parameters reflect relevant cardiac involvement in SSc, and as such can contribute to risk stratification and patient management. Disclosure of Interest: None declared